2015
DOI: 10.3846/bme.2015.220
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking as an Instrument for Improvement of Quality Management in Higher Education

Abstract: Conditioned by globalisation and constant change, higher education institutions (HEIs) are forced to pursue new instruments for quality assurance in higher education. States seem to pursue this aim by attempting to create an efficiently operating system of higher education that satisfies needs of diverse societal groups. Quality dimension is the most important element of efficient and effective higher education. From the perspective of a state, assessment and monitoring of quality are instruments for the manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The result from the structural equation modeling analysis showed that benchmarking and self-assessment enhance the positive contributions of TQM methodologies toward HIEs' research output. Benchmarking as earlier stated occurs when organizations look out for key players in the industry who have made massive improvements over time, to understand their strategies and implement those strategies in their organization if possible [ 29 ]. The findings from this study align with Paliulis & Labanauskis [ 28 ] who asserted that HEIs that create high-profile research output benefit from intensive benchmarking of the global education industry leaders to understand their competitive strategies while creating their unique niche for effective performance.…”
Section: Discussionmentioning
confidence: 99%
“…The result from the structural equation modeling analysis showed that benchmarking and self-assessment enhance the positive contributions of TQM methodologies toward HIEs' research output. Benchmarking as earlier stated occurs when organizations look out for key players in the industry who have made massive improvements over time, to understand their strategies and implement those strategies in their organization if possible [ 29 ]. The findings from this study align with Paliulis & Labanauskis [ 28 ] who asserted that HEIs that create high-profile research output benefit from intensive benchmarking of the global education industry leaders to understand their competitive strategies while creating their unique niche for effective performance.…”
Section: Discussionmentioning
confidence: 99%
“…This research proposes and hypothesizes the role of brands (with the dimensions of quality perception, brand image, integrated marketing communications) in shaping attitudes and influencing college consumer interest. The findings of Paliulis and Labanauskis (2015), indicate that the quality dimension is the most important element of an efficient and effective higher education both with regard to academic and administrative matters. The quality of services for higher education consists of seven criteria: quality of input, curriculum, academic facilities, industry interaction, interaction quality, support facilities, and non-academic processes (Jain et al, 2013).…”
Section: Conceptual Model Development and Hypothesismentioning
confidence: 98%
“…With the presence of a quality assurance team in educational institutions, it is hoped to increase the level of institutions, so that this can be the purpose of the promotion of educational institutions (Kustian et al, 2018;Tijssen et al, 2009). (Paliulis & Labanauskis, 2015) also revealed that benchmarks are effective in improving the quality of performance in higher education institutions and can complement the existing quality management system (Hudson et al, 2010) research in Turkey revealed that there are no student mentoring standards in Turkish educational institutions, thus setting benchmarks for mentoring practices that can help teachers identify student needs so they can develop programs to meet their needs. participants can improve the quality of education in Turkey.…”
Section: Processmentioning
confidence: 99%